Study on the law of air leakage in goaf under the influence of double-series coal seam mining - Yongfu Zhang; Chuanbo Cui; Ran Peng; Wei Li (Heliyon)
In order to solve the engineering problem of a large amount of wind leakage in the 8106 comprehensive mining working face of the Carboniferous System under the influence of overlapping mining of two coal seams in Yongdingzhuang Mine, Datong Mining Area, this paper utilizes finite element numerical simulation software to study the wind leakage characteristics of the 8106 working face and the distribution range of the spontaneous combustion “three zones” of the mining area. The results show that, under the condition of external air leakage, the internal pressure of the goaf is greater than the external pressure, the upper pressure is greater than the lower pressure, and the seepage direction is from the top down and from the inside out. Under the condition of no external air leakage, the air leakage source is mainly concentrated in the air inlet lane. When there is no external air leakage, the goaf oxidation zone is evenly distributed with a width of 70 m. When there is external air leakage, the width of oxidation zone in goaf is between 70 m and 150 m. With the increase of external air leakage, the area and width of oxidation zone on both sides of the inlet and return air duct become larger, which leads to the increase of coal spontaneous combustion risk in coal mining airspace. The research results of this paper have theoretical guidance for air leakage monitoring and fire prevention in goaf.